Ninth Plan 1997-2002 Mid-Term Appraisal Government of Pondicherry - Planning Commission (Planning Commission, 1999)
The territory of Pondicherry merged with Indian Union with effect from 01-11-1954 in accordance with the de-facto agreement between the Government of India and the Government of France, which was signed on 21-10-1954. De-jure transfer of Pondicherry took place on 16th August, 1962. Thereafter the Union Territory of Pondicherry consisting of the regions of Pondicherry, Karaikal, Mahe and Yanam has been administered under the provisions of Government of Union Territories Act, 1963.
Planning and Research Department Pondicherry Government of Pondicherry